A new social street economy : an effect of the COVID-19 pandemic - Grima, Simon; Sirkeci, Osman; Elbeyoğlu, Kamuran (Contemporary studies in economic and financial analysis ;, 2021)
A New Social Street Economy: An Effect of The COVID-19 Pandemic explores the impact of the Corona crisis on the capitalist world and the developments that have taken place throughout the world. Uniquely, this book considers the street economy in terms of how it relates to the social economy and how it contributes to the four main dimensions of social economy; which are supply of needs, social benefit production, fair distribution and sustainability. Reciprocity is the mechanism that makes relational and organizational life possible. When reciprocity finds an economic expression for providing goods and services to people and communities, the conclusion is a working social economy. In these difficult times, we witness both the best and worst aspects of human nature. The street economy is the most basic component, indicator and guarantee of an egalitarian, solidarist, sharing and truly participative social economy and democracy in an epidemic environment that supports all groups in need without questioning the identity or origins of the groups in need.